Social Security and Household Wealth Accumulation: Refined Microeconometric Evidence - Gullason, Edward T.; Kolluri, Bharat R.; Panik, Michael J. (The Review of Economics and Statistics, 1993)
Edward T. Gullason, Bharat R. Kolluri, Michael J. Panik, Social Security and Household Wealth Accumulation: Refined Microeconometric Evidence, The Review of Economics and Statistics, Vol. 75, No. 3 (Aug., 1993), pp. 548-551